P55 Looking for a needle in a Haystack: outcomes of the surrey hepatitis C/PHE lookback exercise. Re-engaging patients in a low prevalence ODN. (28th September 2020) - Mohamed, Osob; Harrod, Elizabeth; Parsons, Margaret; Camarata, Michelle; Westwood, Romanie; Dawes, Yvonne; Street, Karen; Tan, Laiting; Duckhouse, Valerie; Goncalves, Liliana Da Silva; Nigh, Adam; Ho-Yen, Nicola; et al.
Abstract : Introduction: The World Health Organisation has published a strategy for eradication of Hepatitis C (HCV) by 20301. This will require active case finding and re-engagement of people previously diagnosed with HCV. In September 2018, Public Health England (PHE) and NHS England shared details of patients with historical HCV-positive results from sentinel surveillance between 1996 and 2017, requesting that local operational delivery networks (ODNs) contact each person to retest and treat as appropriate. Here we present the data for the Surrey ODN. Methods: The Surrey 'Lookback' cohort included 1162 people. The PHE protocol was utilised with local amendments. Prior to contacting individuals, cases were cross-checked with NHS spine local databases, paper records and laboratory data to exclude deceased patients and those without active viraemia. The remaining patients received a letter explaining the initiative, followed by up to 3 telephone calls before a final letter was sent to the GP to advise that engagement was unsuccessful. Results: Of the initial 1162 patients, 241 were assigned to adjacent ODNs, 19 were deceased. Local laboratory systems allowed us to censor 105 patients with negative RNA following initial positive antibody testing. We made contact with 562/797 (70%) of the remaining patients, of whom 100 (12.5%) patients attended for further investigation and were confirmed PCR negative, 149 (19%) reported successful therapy outside the ODN, 21 (3%) reported documented spontaneous clearance, 12 were antibody and PCR negative (1.5%) four of whom categorically denied ever receiving a prior test, and 18 (2%) declined re-engagement. 5.9% of the total cohort were diagnosed with active HCV requiring further treatment (8.4% of the 562 patients we successfully re-engaged). Sadly, one patient was diagnosed with advanced hepatocellular carcinoma as part of work up following re-engagement. Discussion: Initial anxiety about the potential burden of work from the Lookback exercise was unfounded, as many patients were already known to the team or had already received successful treatment. Each telephone contact enabled re-engagement and a discussion regarding new treatment options for those concerned about side effects from previous treatments. We have accounted for 70% of patients, there may be an opportunity to attempt re-engagement of the missing 225 patients at a future date. Some patients were concerned that they were contacted regarding previous investigations, though the majority were happy to have the opportunity to receive treatment if required. We were able to educate and re-engage 47 patients for treatment, with significant personal and population benefits.